Optimizing Adaptive Rewards Using Sugeno Fuzzy Logic in an Android Educational Game - Ginanjar Setyo Permadi; Tanhella Zein Vitadiar; Chamdan Mashuri (Diponegoro University, 2025)
This study developed an Android-based educational game to teach children about waste management, with an adaptive reward system using Sugeno fuzzy logic. The aim of the study was to increase student motivation and engagement in environmental learning by providing rewards tailored to player performance. The development method referred to the Game Development Life Cycle (GDLC), covering the development stages up to beta testing. Media expert validation results showed good game quality in terms of visual appearance and ease of use, with an average score of 4.6/5. Material validation also showed the suitability of the material for learning objectives with a score of 4.7/5. Trials with 26 primary school students resulted in an average score of 4.6/5 for ease of use and 4.8/5 for visual appeal. The Sugeno fuzzy logic-based reward system proved effective in adjusting rewards to player performance. Test data showed that 70% of students received 3 stars, 20% received 2 stars, and 10% received 1 star. This system increased student motivation and engagement in learning. This research contributes to the development of fuzzy technology-based educational games by demonstrating the great potential of Sugeno fuzzy logic in creating adaptive reward systems that enhance learning. This game is expected to be an effective alternative in teaching waste management and can be expanded to other educational topics.